Analisis Kemampuan Komunikasi Matematis pada Materi Bentuk Aljabar Kelas VII SMP N 1 Utan - Muzaki, Ahmad; Yulianti, Sri (Jurnal Ilmiah IKIP Mataram, 2023)
This study aims to determine the mathematical communication skills in the material of algebraic forms of seventh grade students of SMP Neri 1 Utan. The subjects of this study were students of class VII.1 SMP Negeri 1 Utan, totaling 16 people. The method used is descriptive with a qualitative approach. The data collection technique used in this study was writing consisting of 5 description questions, and interview sheets needed to obtain support data. The tests were conducted to determine students' mathematical communication skills when working on questions, while interviews were used to obtain more in-depth information about students' written mathematical communication skills. The results showed that students' mathematical communication skills in the high category 25% of students were able to achieve all indicators of written mathematical communication skills, while the medium category 56.25% were able to meet 2 indicators of written mathematical communication skills and the low category 18.75% low were able to meet 1-2 indicators of written mathematics communication skills.